2011
DOI: 10.1186/1749-799x-6-64
|View full text |Cite
|
Sign up to set email alerts
|

Flexible intramedullary nailing in paediatric femoral fractures. A report of 73 cases

Abstract: BackgroundFlexible intramedullary nailing has emerged as an accepted procedure for paediatric femoral fractures. Present indications include all patients with femoral shaft fractures and open physis. Despite its excellent reported results, orthopaedic surgeons remain divided in opinion regarding its usefulness and the best material used for nails. We thus undertook a retrospective study of paediatric femoral fractures treated with titanium or stainless steel flexible nails at our institute with a minimum of 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 42 publications
6
32
0
Order By: Relevance
“…In our study the number of patients with normal range of motion at hip and knee in Group 1 was 16 (94.12%), while in Group 2 the number was 17 (100%). Similar results were obtained by the studies of Khazzam et al 9 and Lohiya et al 10 where clinical evaluation revealed full range of motion of the hip and knee in all patients at final follow-up. The average duration of progressing to full weight bearing in our study was 11.6 weeks.…”
Section: Discussionsupporting
confidence: 89%
“…In our study the number of patients with normal range of motion at hip and knee in Group 1 was 16 (94.12%), while in Group 2 the number was 17 (100%). Similar results were obtained by the studies of Khazzam et al 9 and Lohiya et al 10 where clinical evaluation revealed full range of motion of the hip and knee in all patients at final follow-up. The average duration of progressing to full weight bearing in our study was 11.6 weeks.…”
Section: Discussionsupporting
confidence: 89%
“…Pain and skin irritation at the nail insertion site has been encountered, which causes limited movement of the knee, however the problem no longer exists once the nail is removed 13 . One study which consisted of 229 children with 234 diaphyseal fractures of the femur basically showed the most common complication was angulation 16 .…”
Section: Minor Complicationsmentioning
confidence: 99%
“…The entry point of flexible nails is the metaphysis and they are mainly used for paediatric shaft fractures, to avoid damage to the growth plates. In addition, flexible nails allow micromovement 13 and are associated with a lower risk of infection 25 . Previously, this technique was considered to be the appropriate treatment for femoral shaft fractures in patients of age of 6-16 years, but literature suggests that the technique works well for preschool children too, and has also produced exceptional union results.…”
Section: Flexible Im Nails In Pediatricsmentioning
confidence: 99%
“…32,33 ESIN has rapidly become the treatment of choice for pediatric femur fractures because it leads to excellent results and allows rapid ambulation with little risk of osteonecrosis, physeal injury, or refracture. 34 However, excessive shortening leading to protruding nails and discrepancy of leg length as well as the need for unplanned surgical procedures have frequently been described in length-unstable fractures and/ or heavier patients (> 50 kg). 35 Because of its simplicity and ubiquitous application, the ESIN method has been optimized repeatedly to increase stability especially in the lower extremities.…”
Section: Femurmentioning
confidence: 99%